Marketing Strategies In Driving Tourist Growth Based On Travel Experience And Preferences In Tourism Attraction Areas - Khotimah, Khusnul; Mokodompit, Eliyanti Agus; Kusumaningtyas, Daru Putri; Gugat, Rudy Max Damara; Nusran, Muhammad (Jurnal Ekonomi, 2024)
In order to stimulate tourism development in tourist destinations, it is imperative to implement marketing strategies that are informed by traveler preferences and experiences in the rapidly expanding digital era. The literature review method is employed in this study to examine the impact of traveler preferences and experiences on the development of effective marketing strategies. The analysis of the literature indicates that travelers' satisfaction and loyalty can be enhanced by providing them with distinctive and personalized experiences. The collection and comprehension of passenger preferences are significantly influenced by digital technologies, including social media and data analytics. The beneficial effects of implementing experiential marketing strategies are illustrated by case studies in Indonesia, including the "Wonderful Indonesia" program and the utilization of the Traveloka app and social media. In order to establish an environment that fosters sustainability and innovation in the tourism industry, it is imperative that the government, private sector, and local communities provide their support. The findings of this investigation offer profound insights for tourism industry practitioners and policymakers in the development of effective marketing strategies that will enhance traveler satisfaction and loyalty.